2022
DOI: 10.1186/s12885-022-09484-6
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol comparing the ethical, psychological and socio-economic impact of personalised breast cancer screening to that of standard screening in the “My Personal Breast Screening” (MyPeBS) randomised clinical trial

Abstract: Background The MyPeBS study is an ongoing randomised controlled trial testing whether a risk-stratified breast cancer screening strategy is non-inferior, or eventually superior, to standard age-based screening at reducing incidence of stage 2 or more cancers. This large European Commission-funded initiative aims to include 85,000 women aged 40 to 70 years, without prior breast cancer and not previously identified at high risk in six countries (Belgium, France, Italy, Israel, Spain, UK). A speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…A study exploring views of low-risk women found this approach overall to be acceptable if extending intervals ensured informed choice, is grounded in evidence-based, and is carefully communicated[ 36 ]. Other qualitative studies are also underway exploring low-risk women’s views[ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study exploring views of low-risk women found this approach overall to be acceptable if extending intervals ensured informed choice, is grounded in evidence-based, and is carefully communicated[ 36 ]. Other qualitative studies are also underway exploring low-risk women’s views[ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further necessary requirement has been the development of criteria to categorise woman into specified risk-groups such as low, population risk or high-risk of developing breast cancer in a specified time period (ten-year or life-time). Collectively, the ability to identify a women's risk of breast cancer, approaches to the feedback of individual risk and actions to suggest given the defined risk-category has stimulated interest and the generation of evidence to support the introduction or risk-NBSP (5)(6)(7)(8)(9)(10). To date, there are no examples of a risk-NBSP used in practice but there is consensus about the need for different types of evidence to support their introduction (11).…”
Section: Introductionmentioning
confidence: 99%
“…Over 200 single nucleotide polymorphisms (SNPs) associated with breast cancer risk have been identified . Ongoing prospective trials are testing the ability of the PRS to inform decision-making around breast cancer screening and prevention [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%